Scratch-resistant varnish as well as preparation method and application thereof

By designing a varnish with a core-shell structure that does not contain wax and glass powder, and using specific components and film forming additives to form a multi-dimensional cross-linked three-dimensional structure, the existing imitation stone coatings have solved the shortcomings in stain resistance, water resistance and permeability, and achieved good scratch resistance and water resistance.

CN119875455APending Publication Date: 2025-04-25NIPPON PAINT GUANGZHOU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510006144.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing imitation stone coatings have shortcomings in terms of stain resistance, water resistance and permeability, and usually require matching cover varnish to improve these problems, but this will increase the construction steps and difficulty.

Method used

Using varnish without wax and glass powder, the core-shell structure is designed in the emulsion, and the core-shell part is composed of methyl methacrylate, butyl acrylate, glycidyl methacrylate and other core parts are composed. The coupling agent-modified nano-silicon dioxide forms the shell part and is combined with alcohol esters film forming additives to form a multi-dimensional cross-linked three-dimensional structure to improve scratch resistance and water resistance.

Benefits of technology

It achieves good scratch resistance, water resistance and stain resistance on the basis of ensuring the fullness and permeability of the paint film, and avoids the defects that increase construction steps and difficulty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875455A_ABST
    Figure CN119875455A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and particularly relates to scratch-resistant varnish as well as a preparation method and application thereof. The varnish comprises an emulsion, an auxiliary agent and water, the emulsion has a core-shell structure; the core of the core-shell structure comprises methyl methacrylate, butyl acrylate and glycidyl methacrylate, and the shell of the core-shell structure comprises coupling agent modified nano silicon dioxide; the auxiliary agent comprises a film-forming auxiliary agent, and the film-forming auxiliary agent comprises an alcohol ester compound; the alcohol ester compound comprises a diisobutyl ester substance and alcohol ester 12. According to the invention, the specific emulsion with a core-shell structure is adopted, so that better scratch resistance can still be obtained even if wax, glass powder and other scratch-resistant auxiliaries are not added, and the paint has good stain resistance, permeability, water resistance and early water resistance. Meanwhile, the emulsion with a core-shell structure is matched with a specific type of coalescing agent, so that a multi-dimensional cross-linked stereo structure can be obtained during film forming, the hardness is high, the surface tension is small, the friction force is small during contact with a foreign object, and the scratch resistance and the stain resistance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and particularly relates to a scratch-resistant varnish and a preparation method and application thereof. Background Art

[0002] During the construction of exterior wall imitation stone paint, since imitation stone paint generally has problems such as poor stain resistance, poor water resistance, insufficient permeability and gloss, it is generally necessary to use a matching topcoat varnish to improve these problems.

[0003] At present, in order to meet the market demand for excellent scratch resistance, stain resistance and water resistance of varnish, some manufacturers have launched anti-scratch varnishes that usually add some anti-scratch additives such as wax and glass powder to high-hardness varnish to improve scratch resistance, but this often has an adverse effect on the fullness and permeability of the paint film, and increases the construction steps and difficulty. Summary of the invention

[0004] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides a varnish which does not add anti-scratch additives such as wax and glass powder, and has good scratch resistance, water resistance and stain resistance on the basis of ensuring the fullness and permeability of the paint film.

[0005] The inventive concept of the present invention: the varnish of the present invention includes an emulsion, an additive, and water; the emulsion has a core-shell structure; the core of the core-shell structure includes methyl methacrylate, butyl acrylate, and glycidyl methacrylate, and the shell of the core-shell structure includes nano-silicon dioxide modified by a coupling agent. The additive includes a film-forming additive, and the film-forming additive includes an alcohol ester compound; the alcohol ester compound includes diisobutyl ester substances and alcohol ester twelve. The emulsion of the present invention has a core-shell structure, and the core is formed by a reasonable combination of soft and hard monomers. The silicon-carbon structure introduced in the shell provides a lower surface tension and reduces friction resistance. Even if no additional anti-scratch additives such as wax and glass powder are added, better scratch resistance and water resistance can still be obtained. Since anti-scratch additives such as wax and glass powder are not included, the singleness of the effective ingredients of the varnish is guaranteed, thereby ensuring permeability and fullness. The pore structure of the silicone component in the shell allows air to enter and exit, prevents water molecules from entering, and has good water resistance and stain resistance. The emulsion with a core-shell structure is combined with a specific type of film-forming aid. When forming a film, it can form a multi-dimensional cross-linked three-dimensional structure from bottom to surface and from inside to outside. It has high hardness, low surface tension, low friction when in contact with foreign objects, and excellent scratch resistance and stain resistance. In addition, the specific core-shell structure design makes the early paint film strength fast and the early water resistance good.

[0006] Accordingly, a first aspect of the present invention provides a scratch resistant varnish.

[0007] Specifically, the scratch-resistant varnish includes an emulsion, an additive, and water;

[0008] The emulsion has a core-shell structure; the core of the core-shell structure comprises methyl methacrylate, butyl acrylate and glycidyl methacrylate, and the shell of the core-shell structure comprises nano-silicon dioxide modified by a coupling agent.

[0009] The auxiliary agent includes a film-forming auxiliary agent, and the film-forming auxiliary agent includes an alcohol ester compound; the alcohol ester compound includes diisobutyl ester substances and alcohol ester dodeca(C-12).

[0010] Preferably, in the core of the core-shell structure, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is (3-5):(6-8):1; further preferably, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is (3.5-4.5):(6.5-7.5):1; further preferably, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is 4:7:1.

[0011] Preferably, the emulsion is RS8701 emulsion of Badful.

[0012] Preferably, the coupling agent includes a silane coupling agent; further preferably, the coupling agent includes γ-methacryloxypropyltrimethoxysilane (KH570).

[0013] Preferably, the additive further comprises at least one of a multifunctional additive, a rheological additive, a defoaming agent, a pH regulator, an antifreeze agent, an antifungal agent and a bactericide.

[0014] Preferably, the additives also include multifunctional additives, rheological additives, defoaming agents, pH regulators, antifreeze agents, mildew and algae inhibitors and preservatives; and in parts by weight, the coating includes 45-75 parts of emulsion, 0.1-6.5 parts of multifunctional additives, 0.27-3.3 parts of rheological additives, 0.1-0.65 parts of defoaming agents, 0.1-0.55 parts of pH regulators, 4.5-11 parts of film-forming additives, 0.27-1.1 parts of antifreeze agents, 0.1-1.1 parts of mildew and algae inhibitors, 0.1-0.33 parts of fungicides, and 9-22 parts of water.

[0015] Further preferably, the coating includes, by weight, 50-70 parts of emulsion, 0.1-6.2 parts of multifunctional additive, 0.3-3.0 parts of rheological additive, 0.1-0.6 parts of defoaming agent, 0.1-0.5 parts of pH regulator, 5-10 parts of film-forming aid, 0.3-1.0 parts of antifreeze agent, 0.1-1.0 parts of mildew and antialgae agent, 0.1-0.3 parts of bactericide, and 10-20 parts of water.

[0016] Preferably, the multifunctional additive comprises an organic-inorganic hybrid high molecular polymer, and the multifunctional additive is a polymer / inorganic nano-material composite additive that can significantly improve multiple properties of water-based coatings.

[0017] Preferably, the inorganic component in the organic-inorganic hybrid polymer includes at least one of SiO2 and TiO2 nanoparticles.

[0018] Preferably, the particle size of the inorganic component is 4.5-22 nm; more preferably, the particle size of the inorganic component is 5-20 nm.

[0019] Preferably, the structural formula of the organic component in the organic-inorganic hybrid polymer is:

[0020]

[0021] Wherein, the R is a trimethyl carbon chain, and the n is 40-60.

[0022] Specifically, the organic component has a certain degree of crosslinking and network structure. By controlling the type and polarity of the functional group R in the polymer, controlling the hydrogen bond balance between the hydrophobic main chain and the surrounding water molecules, the fluid volume of the polymer itself is increased, and the space for free movement of particles is reduced, thereby increasing the viscosity of the system. At the same time, by regulating the size of the molecular weight, the entanglement of the molecular chain achieves an increase in viscosity. The order-disorder transition of the polymer chain is utilized to achieve high viscosity under low shear in static state, and low viscosity under high shear. In addition, by forming micelles, the micelles and particles associate to form a network structure, so that the viscosity of the system is increased, and the rheological properties of the coating can also be improved.

[0023] Preferably, the rheological additive comprises a non-ionic polyurethane polymer.

[0024] Preferably, the defoaming agent includes at least one of a mineral oil defoaming agent and a silicone defoaming agent.

[0025] Preferably, the pH adjuster comprises an amine adjuster.

[0026] Preferably, the thickener comprises a polyurethane thickener.

[0027] Preferably, the antifreeze agent comprises propylene glycol.

[0028] Preferably, the fungicide includes at least one of 2-n-octyl-4-isothiazolin-3-one (BIT), 2-methyl-4-isothiazolin-3-one (MIT) and 5-chloro-2-methyl-4-isothiazolin-3-one (CIT).

[0029] Preferably, the mildew and algae preventer comprises a Kathon mildew preventer.

[0030] The second aspect of the present invention provides a method for preparing the scratch-resistant varnish according to the first aspect of the present invention.

[0031] Specifically, the method for preparing the scratch-resistant varnish comprises the following steps:

[0032] The various raw material components are mixed to prepare the scratch-resistant varnish.

[0033] Preferably, the method for preparing the scratch-resistant varnish comprises the following steps:

[0034] (1) stirring the multifunctional auxiliary agent, defoaming agent, antifreeze agent, pH regulator, part of water and part of emulsion to obtain a mixed solution A;

[0035] (2) adding the remaining emulsion to the mixed solution A obtained in step (1), stirring evenly, to obtain a mixed solution B;

[0036] (3) adding the film-forming aid, thickener and remaining water to the mixed solution B obtained in step (2), stirring evenly to obtain a mixed solution C;

[0037] (4) Adding the bactericide and anti-mildew and anti-algae agent to the mixed solution C obtained in step (3), stirring evenly, and obtaining the scratch-resistant varnish.

[0038] Preferably, in step (1) and step (2), the stirring speed is 270-450 rpm; further preferably, in step (1) and step (2), the stirring speed is 300-400 rpm.

[0039] Preferably, in step (1), the mass fraction of the partial water to the total water is 80-95%, and the mass fraction of the partial emulsion to the total emulsion is 15-28%.

[0040] Preferably, in step (3) and step (4), the stirring speed is 700-1100 rpm; further preferably, in step (3) and step (4), the stirring speed is 800-1000 rpm.

[0041] Preferably, the method for preparing the emulsion comprises the following steps:

[0042] (1) mixing water, an emulsifier, and an initiator, heating the mixture, then adding an acrylic acid monomer, raising the temperature, and maintaining the temperature to obtain a mixture;

[0043] (2) adding the coupling agent-modified nano-silica to the mixture obtained in step (1), keeping the mixture warm, and adjusting the pH to alkaline to obtain the emulsion.

[0044] Preferably, in step (1), the emulsifier includes at least one of alkylphenol polyoxyethylene ether (OP-10) and sodium dodecylbenzene sulfonate; further preferably, in step (1), the emulsifier includes OP-10 and sodium dodecylbenzene sulfonate.

[0045] Preferably, the molar ratio of OP-10 to sodium dodecylbenzene sulfonate is 1:(1.6-2.5); further preferably, the molar ratio of OP-10 to sodium dodecylbenzene sulfonate is 1:(1.8-2.2); further preferably, the molar ratio of OP-10 to sodium dodecylbenzene sulfonate is 1:2.

[0046] Preferably, in step (1), the initiator comprises potassium persulfate.

[0047] Preferably, in step (1), the heating temperature is 50-70°C; further preferably, the heating temperature is 55-65°C; further preferably, the heating temperature is 60°C.

[0048] Preferably, the acrylic monomers include methyl methacrylate, butyl acrylate and glycidyl methacrylate.

[0049] Preferably, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is (3-5):(6-8):1; further preferably, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is (3.5-4.5):(6.5-7.5):1; further preferably, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is 4:7:1.

[0050] Preferably, in step (1), the amount of the initiator used is 2-3‰ of the total mass of the acrylic acid monomer; further preferably, in step (1), the amount of the initiator used is 2.2-2.7‰ of the total mass of the acrylic acid monomer; further preferably, in step (1), the amount of the initiator used is 2.5‰ of the total mass of the acrylic acid monomer.

[0051] Preferably, in step (1), the insulation temperature is 70-90°C, and the insulation time is 25-35 min; further preferably, in step (1), the insulation temperature is 75-85°C, and the insulation time is 27-33 min; further preferably, in step (1), the insulation temperature is 80°C, and the insulation time is 30 min.

[0052] Preferably, in step (2), the amount of the coupling agent-modified nano-silica is 8-12% of the mass of the acrylic acid monomer; further preferably, in step (2), the amount of the coupling agent-modified nano-silica is 9-11% of the mass of the acrylic acid monomer; further preferably, in step (2), the amount of the coupling agent-modified nano-silica is 10% of the mass of the acrylic acid monomer.

[0053] Preferably, the preparation method of the coupling agent modified nano-silica is to mix tetraethyl orthosilicate and anhydrous ethanol, heat for the first time, adjust the pH to acidic, add water, heat for the second time, then add the coupling agent, stir, and distill at low pressure to obtain the coupling agent modified nano-silica.

[0054] Preferably, the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and water is (15-19): (4.5-6.5): 2; further preferably, the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and water is 17.5: (5-6): 2; further preferably, the mass ratio of tetraethyl orthosilicate, anhydrous ethanol and water is 17.5: 5.5: 2.

[0055] Preferably, the temperature of the first heating is 50-70°C; further preferably, the temperature of the first heating is 55-65°C; further preferably, the temperature of the first heating is 60°C.

[0056] Preferably, the pH is 3-5; further preferably, the pH is 3.5-4.5; further preferably, the pH is 4.

[0057] Preferably, the temperature of the second heating is 70-90°C; further preferably, the temperature of the second heating is 75-85°C; further preferably, the temperature of the second heating is 80°C.

[0058] Preferably, the second heating to the temperature is followed by stirring, and the stirring time is 2.5-3.5 h; further preferably, the stirring time is 2.7-3.3 h; further preferably, the stirring time is 3 h.

[0059] Preferably, the amount of the coupling agent is 16-25% of the mass of the tetraethyl orthosilicate; further preferably, the amount of the coupling agent is 18-22% of the mass of the tetraethyl orthosilicate; further preferably, the amount of the coupling agent is 20% of the mass of the tetraethyl orthosilicate.

[0060] Preferably, the stirring time after adding the coupling agent is 4-6 hours; further preferably, the stirring time after adding the coupling agent is 4.5-5.5 hours; further preferably, the stirring time after adding the coupling agent is 5 hours.

[0061] Preferably, the coupling agent includes γ-methacryloxypropyltrimethoxysilane (KH570).

[0062] Specifically, the purpose of the reduced pressure distillation is to evaporate excess solvents such as ethanol.

[0063] Preferably, in step (2), the insulation time is 2.5-3.5 h; further preferably, in step (2), the insulation time is 2.7-3.3 h; further preferably, in step (2), the insulation time is 3 h.

[0064] The third aspect of the present invention provides a use of the scratch-resistant varnish according to the first aspect of the present invention in the field of architecture.

[0065] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0066] (1) The emulsion of the present invention has a core-shell structure. The core is formed by a reasonable combination of soft and hard monomers. The silicon-carbon structure introduced in the shell provides a lower surface tension and reduces friction resistance. Even without adding additional anti-scratch additives such as wax and glass powder, better scratch resistance, permeability and water resistance can still be obtained. Since it does not contain anti-scratch additives such as wax and glass powder, the singleness of the effective ingredients of the varnish is guaranteed, thereby ensuring permeability and fullness; and the pore structure of the organic silicon component in the shell allows air to enter and exit, preventing water molecules from entering, and having good water resistance and stain resistance. At the same time, the emulsion with a core-shell structure is matched with a specific type of film-forming additive, and a multi-dimensional cross-linked three-dimensional structure from bottom to surface and from inside to outside can be formed during film formation, with high hardness, low surface tension, low friction when in contact with foreign objects, and excellent scratch resistance and stain resistance; in addition, the specific design of the core-shell structure makes the early paint film strength fast and the early water resistance good.

[0067] (2) The present invention reasonably matches the type and amount of the film-forming aid with the type of monomer in the emulsion. During the film-forming process, the glass transition temperature changes linearly, the film-forming speed is faster, and the film-forming surface is smoother and more glossy.

[0068] (3) The present invention optimizes the type and amount of surfactants (such as defoamers, film-forming aids, multifunctional aids, pH regulators, thickeners, and antifreeze agents) to reasonably match them with the hydrophilic substances in the emulsion, so that the surfactants are evenly distributed throughout the coating film. When immersed in water, the hydrophilic part can adjust the osmotic pressure of water to avoid the formation of water molecules gathering in a certain area, causing whitening, and improving water resistance. In addition, considering the influence of the above-mentioned surfactants on the film-forming process, the reasonable amount of each component is determined, which not only ensures the establishment of early strength of the coating and excellent water resistance during the film-forming process, but also does not affect the density of the final film, and has good stain resistance and high hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 This is a diagram showing the early low-temperature water resistance effect of the varnish of Example 1 of the present invention and Comparative Examples 1-2 after matching construction. DETAILED DESCRIPTION

[0070] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0071] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0072] The sources of the raw material components of the varnishes of Examples 1-3 and Comparative Examples 1-4 of the present invention are as follows:

[0073] RS 8701 emulsion: purchased from Badfu;

[0074] Multifunctional additive A605: purchased from Shanghai Jinzhe New Material Technology Co., Ltd.;

[0075] Defoamer FOAMSTAR ST 2410AG: purchased from BASF;

[0076] Fungicide D29A: purchased from Hofmann;

[0077] Bactericide BT: purchased from Hofmann;

[0078] Antifungal and antialgae agent AA146: purchased from LANXESS;

[0079] pH adjuster AMP-95: purchased from Angus;

[0080] Coalescent COASOL 290: purchased from Dow;

[0081] Thickener ACRYSOL RM-8W: purchased from Yale Shun;

[0082] Wax additive 497: purchased from BYK.

[0083] The raw material components and amounts of the varnishes of Examples 1-3 of the present invention are shown in Table 1.

[0084] Table 1: Raw material components and dosage of varnishes in Examples 1-3 (parts by weight)

[0085] raw material Example 1 Example 2 Example 3 Pure water (amount to be added first) 14.5 19 12 Emulsion RS 8701 (amount to be added first) 12 14 20 A605 multifunctional additive 0.1 0.1 0.2 Defoamer FOAMSTAR ST 2410AG 0.1 0.1 0.1 Fungicide D29A 0.09 0.09 0.09 Fungicide BT 0.09 0.09 0.09 Antifungal and antialgae agent AA146 0.6 0.6 0.6 Propylene glycol 1 1 1 pH Adjuster AMP-95 0.1 0.1 0.1 Emulsion RS 8701 (amount added later) 60 55 55 Film-forming aid C-12 5.6 5 5.6 COASOL 290 2.6 2.5 2.8 Thickener ACRYSOL RM-8W 0.1 0.1 0.1 Pure water (amount to be added later) 2.62 1.82 1.82

[0086] The method for preparing the varnish in Examples 1-3 comprises the following steps:

[0087] (1) The multifunctional auxiliary agent, defoaming agent, antifreeze agent, pH adjuster, part of pure water and emulsion (the amount of emulsion and amount of pure water added first in Table 1) are stirred uniformly to prepare a mixed solution A;

[0088] (2) adding the remaining emulsion (the amount of emulsion added later in Table 1) to the mixed solution A obtained in step (1), stirring evenly, to obtain a mixed solution B;

[0089] (3) adding the film-forming aid, thickener and the remaining pure water (the amount of water added later in Table 1) to the mixed solution B obtained in step (2), stirring evenly, to obtain a mixed solution C;

[0090] (4) Adding a fungicide and an anti-mildew and anti-algae agent to the mixed solution C obtained in step (3), stirring evenly, and preparing a scratch-resistant varnish.

[0091] Comparative Example 1

[0092] The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses a conventional core-shell emulsion (BLJ-9055 of Shanghai Baolijia Chemical Co., Ltd.) to replace the emulsion 8701 of Example 1 in an equal amount, the shell in the BLJ-9055 core-shell emulsion includes methyl methacrylate, the core includes ethyl acrylate, and the rest is the same as Example 1.

[0093] Comparative Example 2

[0094] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses an equal amount of film-forming aid C-12 to replace the film-forming aid COASOL 290, and the rest is the same as Example 1.

[0095] Comparative Example 3

[0096] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses an equal amount of film-forming aid COASOL 290 to replace the film-forming aid C-12, and the rest is the same as Example 1.

[0097] Comparative Example 4

[0098] The difference between Comparative Example 4 and Example 1 is that 4971 parts of wax additives are added in Comparative Example 4, and the amount of pure water used is 1.62 parts, and the rest is the same as Example 1.

[0099] Performance Testing

[0100] The varnishes prepared in Examples 1-3 and Comparative Examples 1-4, or the paint films prepared from the varnishes, were subjected to performance tests. The specific test items and test methods are shown in Table 1.

[0101] Table 1: Test items and test methods

[0102]

[0103]

[0104] Early water resistance at room temperature: Cut a black polyester plastic sheet into 150mm×50mm, make a film on it with a 100-micron wire rod, and then soak it in water at 25°C for 3h; the film making method for the water spray test is the same as above, and then fix it on an asbestos-free fiber cement flat plate and spray it with water at 25°C for 3h; evaluate water resistance using two evaluation dimensions: water spraying and soaking.

[0105] Early water resistance at low temperature: Cut the black polyester plastic sheet into 150mm×50mm, make a film on it with a 100-micron wire rod, and then soak it in water at 5℃ for 3h.

[0106] When analyzing Comparative Examples 1-4, if the standard test method cannot compare the differences between the embodiments and the comparative examples, the soaking time must be extended until the differences between the embodiments and the comparative examples are tested.

[0107] In addition, the test method for scratch resistance is: different personnel use a spatula fixed at a suitable starting angle, try to make the initial angle between the paint film and the spatula 45°, scratch in a single direction for a total of 10 times, observe the severity of the scratch, and score according to the severity of the scratch, with a uniform surface without scratches of 5 points, a slight surface scratch of 4 points, a relatively serious surface scratch of 3 points, a serious surface scratch of 2 points, and a surface damage of 1 point. The performance test results of the varnish of Example 1 and Comparative Examples 1-4 are shown in Table 2.

[0108] Table 2: Performance test results of varnishes of Example 1 and Comparative Examples 1-4

[0109]

[0110] The test results are measured at a temperature of 23±2°C and a humidity of 50±5%.

[0111] NG in early water resistance indicates severe whitening, and there is shedding when the immersion time is extended to 6 hours.

[0112] It can be seen from Table 1 that the varnish prepared by the present invention has good stain resistance, scratch resistance, water resistance, early water resistance, and has good comprehensive properties such as alkali resistance, scrub resistance, temperature change resistance, and construction performance.

[0113] Comparative Example 1 uses the conventional core-shell emulsion BLJ-9055 of Shanghai Baolijia Chemical Co., Ltd. to replace the emulsion 8701 of Example 1 in equal amounts, so that the stain resistance and scratch resistance of Comparative Example 1 are lower than those of Example 1.

[0114] Comparative Example 2 uses an equal amount of film-forming aid C-12 to replace the film-forming aid COASOL 290, and Comparative Example 3 uses an equal amount of film-forming aid COASOL 290 to replace the film-forming aid C-12, so that the stain resistance, scratch resistance, early low-temperature water resistance, and early room-temperature water resistance of the paint films of Comparative Examples 2 and 3 are lower than those of Example 1. It shows that the film-forming aid C-12 and COASOL 290 are indispensable, and the combination of the two can make the paint film have good stain resistance, scratch resistance, and early water resistance.

[0115] Comparative Example 4 adds a wax additive, which makes Comparative Example 4 have poor permeability, that is, poor light transmittance and haze.

[0116] The performance of the varnish of Examples 2-3 is similar to that of Example 1.

[0117] The low-temperature early water resistance of Example 1 and Comparative Example 1-2 after the supporting construction of the varnish was tested, wherein the supporting construction is the supporting use of primer, mid-coat and varnish, and the supporting construction is specifically as follows: use a special primer for sand and gravel to brush apply one coat according to the consumption in the instructions, and cure for 2 hours under standard conditions (temperature (23±2)°C, humidity (50±5)%); mid-coat rock color, the consumption refers to the instructions, and cure for 7 days; finally, apply varnish, the varnish consumption is 0.1kg per square meter, and it is cured at 5°C for 8 hours, and then soaked in water at 5°C for 16 hours, and observe the whitening, shedding and blistering phenomena.

[0118] Example 1, Comparative Example 1-2 Early low temperature water resistance after varnish matching construction Figure 1 As shown by Figure 1 It can be seen that the paint films of Comparative Examples 1 and 2 appear white, indicating that the early low-temperature water resistance of the varnish of Comparative Examples 1-2 is worse than that of Example 1.

[0119] In summary, the present invention adopts a specific emulsion with a core-shell structure, which can still obtain better scratch resistance even without adding anti-scratch additives such as wax and glass powder, and has good stain resistance, permeability, water resistance and early water resistance; at the same time, the emulsion with a core-shell structure is matched with a specific type of film-forming additive, and a multi-dimensional cross-linked three-dimensional structure from bottom to surface and from inside to outside can be formed during film formation, which has high hardness, low surface tension, and low friction when in contact with foreign objects, thereby improving scratch resistance and stain resistance.

[0120] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A varnish, characterized in that: Including emulsion, additives, water; The emulsion has a core-shell structure; the core of the core-shell structure comprises methyl methacrylate, butyl acrylate and glycidyl methacrylate, and the shell of the core-shell structure comprises nano-silicon dioxide modified by a coupling agent. The auxiliary agent includes a film-forming auxiliary agent, and the film-forming auxiliary agent includes an alcohol ester compound; the alcohol ester compound includes diisobutyl ester substances and alcohol ester dodecahydrate.

2. The varnish according to claim 1, characterized in that In the core of the core-shell structure, the molar ratio of methyl methacrylate, butyl acrylate and glycidyl methacrylate is (3-5):(6-8):

1.

3. The varnish according to claim 1, characterized in that The coupling agent includes a silane coupling agent.

4. The varnish according to claim 1, characterized in that The additives also include at least one of a multifunctional additive, a rheological additive, a defoaming agent, a pH regulator, an antifreeze agent, an anti-mildew and anti-algae agent, and a bactericide.

5. The varnish according to claim 4, characterized in that The additives also include multifunctional additives, rheological additives, defoaming agents, pH regulators, antifreeze agents, mildew and algae inhibitors and fungicides; and by weight, the coating includes 45-75 parts of emulsion, 0.1-6.5 parts of multifunctional additives, 0.27-3.3 parts of rheological additives, 0.1-0.65 parts of defoaming agents, 0.1-0.55 parts of pH regulators, 4.5-11 parts of film-forming additives, 0.27-1.1 parts of antifreeze agents, 0.1-1.1 parts of mildew and algae inhibitors, 0.1-0.33 parts of fungicides and 9-22 parts of water.

6. The varnish according to claim 4, characterized in that The multifunctional additive includes an organic-inorganic hybrid polymer; and / or, the rheological additive includes a non-ionic polyurethane polymer; and / or, the defoamer includes at least one of a mineral oil defoamer and a silicone defoamer; and / or, the pH regulator includes an amine regulator.

7. The method for preparing the varnish according to any one of claims 1 to 6, characterized in that: The following steps are involved: The varnish is prepared by mixing various raw material components.

8. The preparation method according to claim 7, characterized in that: The preparation method of the emulsion comprises the following steps: (1) mixing water, an emulsifier, and an initiator, heating the mixture, then adding an acrylic acid monomer, raising the temperature, and maintaining the temperature to obtain a mixture; (2) adding the coupling agent-modified nano-silica to the mixture obtained in step (1), keeping the mixture warm, and adjusting the pH to alkaline to obtain the emulsion.

9. The preparation method according to claim 8, characterized in that: In step (1), the emulsifier includes at least one of alkylphenol polyoxyethylene ether and sodium dodecylbenzene sulfonate; and / or the initiator includes potassium persulfate; and / or the heating temperature is 50-70° C.; and / or the acrylic monomer includes methyl methacrylate, butyl acrylate, glycidyl methacrylate; and / or the insulation temperature is 70-90° C. and the insulation time is 25-35 min; And / or, in step (2), the amount of the coupling agent-modified nano-silica is 8-12% of the mass of the acrylic acid monomer; and / or, the insulation time is 2.5-3.5 hours.

10. Use of the varnish according to any one of claims 1 to 6 in the field of construction.

Citation Information

Patent Citations

  • Polyacrylate / nano SiO2 hybrid emulsion with high coating film hardness and tolerance and preparation method for polyacrylate / nano SiO2 hybrid emulsion and application of polyacrylate / nano SiO2 hybrid emulsion

    CN105367702A

  • Waterborne wood coating as well as preparation method and use method thereof

    CN114316702A